Modelling and frequency response analysis of permanent magnet synchronous machine with battery energy storage system - Henri (2016)
With the advancement of electric vehicles, permanent magnet synchronous motor (PMSM) has been gaining popularity for its small size, light weight and high power density. A double-star six-phase PMSM is commonly used for its advantage of being fault tolerant. This project researches on the dc-link side of the double-star PMSM drive with battery energy storage system. The dynamics of dc-link current and voltage are analysed through analytical calculation as well as simulation model. Commonly used motor control methods and inverter modulation strategies are also presented. The calculation of dc-link current and voltage ripples to a six-phase system is also developed from a three-phase system. Simulation results of a double-star system from Matlab/Simulink model are studied, which prove the calculation through the use of dc-link capacitor.